ADVANTAGES OF USING PEDAGOGICAL TECHNOLOGY IN THE SUBJECT OF NATURE INTRODUCTION IN A PRESCHOOL EDUCATIONAL INSTITUTION - Mamahanova Jumagul Niyozbekovna (Journals Park Publishing, 2022)
In the article, all innovative innovations in education for children serve to increase the effectiveness of teaching. The appropriate use of new pedagogical technologies in preschool education increases the effectiveness of teaching. The article describes pedagogical technologies.
Keywords: Interactive method, ICT educational tools, dynamic and static slides, ecology, fruits.